Using Speechace Web To Help EFL Learners Improving Speaking Skill - Abdul Muhyi Muhyi; Tenika Illananingtyas (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Technology is increasingly being used in EFL classrooms and has also changed the interaction between teachers and students. Especially in English-speaking countries, AI innovation has progressively coordinated dialect learning and appraisal, advertising productivity and locking in the environment. One of the easiest to use and most widely used from a practical perspective is the web-based one called Speechace, which uses speech recognition to assess and train English-speaking skills to provide immediate feedback and has guided practice that can be done at any time. This study seeks to investigate the efficacy of Speechace in developing EFL learners’ speaking skills through a literature review. Following the literature review method, the authors reviewed books, journal articles, and reputable online sources that clearly explain how the platform helps students’ pronunciation, fluency, and motivation in learning English. The findings show that Speechace’s immediate individual feedback allows learners to self-identify and self-correct their mistakes and improve their general speaking skills. In addition, consistent use of the technology-enabled platform also encourages self-directed learning and builds learners’ confidence and insight in speaking English. Findings show that when non-native speakers use Speechace consistently, treating it as a daily practice buddy for students reluctant to speak English, the program fits more good and naturally into regular EFL classes.